The Contribution Of Learning Concentration And Self-Efficacy To Students' Understanding Of Material At Ma As-Sa'adah Lampah, Kedamean Gresik - Yulianto; Didit Darmawan (Hikamatzu | Journal of Multidisciplinary, 2024)
This research aims to investigate the influence of learning concentration and self-efficacy on students' understanding of material at MA As-Sa'adah Lampah Kedamean Gresik. By using a quantitative approach, this research aims to measure the extent to which independent variables, namely learning concentration and self-efficacy, influence students' understanding of material at the institution. The research population involved all students at MA As-Sa'adah Lampah Kedamean Gresik, totaling 65 students, and all were considered as respondents to ensure maximum representation. Data analysis uses multiple linear regression statistical techniques to assess the extent to which learning concentration and self-efficacy can predict students' understanding of the material. Research findings reveal that learning concentration and self-efficacy make a significant contribution to students' understanding of the material. These results can provide valuable guidance for learning approaches that can increase the effectiveness of the learning process at MA As-Sa'adah Lampah Kedamean Gresik by paying attention to aspects of learning concentration and developing student self-efficacy